Pengaruh Modal Sosial terhadap Fungsi Kognitif pada Pasien Skizofrenia di RSUD dr. Soeselo - Glorio Immanuel; Prima Maharani Putri; Irma Finurina Mustikawati (Syntax Corporation Indonesia, 2021)
This study wanted to look at the relationship and influence of social capital on cognitive function in schizophrenic patients. Social capital is a concept that arises from the results of interaction in society with a long process and is believed to be one of the main components in driving togetherness, mobility of ideas, mutual trust and mutual benefit to achieve mutual progress. Interactions that form networks in togetherness in social capital contain norms, values and mutual understanding that facilitate cooperation in a group. Social capital is generally associated with health and is considered an important etiology in schizophrenia where in the early stages of schizophrenia there are significant cognitive symptoms making it very difficult for people with the disorder to work, study or work in social life. This research method uses the design of latitude cut study, conducted in dr. hospital. soeselo and using MMSE instruments. The results of the study found a link between social capital and cognitive symptoms in schizophrenic patients where in individuals with good social capital was shown to better adjust to cognitive function. Conclusions on individuals with good social capital can adjust better because individuals have had better coping, perception and adjustment about themselves and their environment, individuals already have the ability to maintain their communication and interaction in public life.